VOC 202012/01 Variant Is Effectively Neutralized by Antibodies Produced by Patients Infected before Its Diffusion in Italy - Rondinone, Valeria (Viruses, 2021)
The coronavirus disease 2019 (Covid-19) pandemic is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and presents a global health emergency that needs urgent intervention. Viruses constantly change through mutation, and new variants of a virus are expected to occur over time. In the United Kingdom (UK), a new variant called B.1.1.7 has emerged with an unusually large number of mutations. The aim of this study is to evaluate the level of protection of sera from 12 patients infected and later healed in Apulia Region (Italy) with Covid-19 between March and November 2020, when the English variant was not circulating in this territory yet, against the new VOC 202012/01 variant by seroneutralization assay. The sera of patients had already been tested before, using a virus belonging to the lineage B.1 and showed an antibody neutralizing titer ranging between 1:160 and 1:320. All the 12 sera donors confirmed the same titers of neutralizing antibodies obtained with a strain belonging to the lineage B.1.1.7 (VOC 202012/01). These data indicate that antibodies produced in subjects infected with variants of Sars-CoV-2 strain before the appearance of the English one, seem to have a neutralizing power also against this variant.